A Feasibility study paper for Acutensils - Macusasa, Wendylyn O., Melanio, Marc Johnsen C. Quinto, Judee Mary T., Sanchez, Erica Jane S. Tolentino, Marc Johnino B. 4 0 16; 5
SUMMARY: ACUTENSILS is a company that creates beautiful and sustainable kitchen utensils from acacia wood. Their utensils are not only good for the environment, but they are also durable, heat-resistant, and naturally antibacterial. ACUtensils is a great choice for people who are looking for an eco-friendly alternative to plastic utensils. The AcUtensil brand is more than just utensils; It's a choice for a healthy world. We make beautiful, long-lasting wooden tools that can be used for every meal instead of plastic ones. Are you sick of adding to plastic pollution? One tasty bite at a time, AcUtensil gives you the power to make a difference. These tools are not only good for the environment, but they also add a warm and natural beauty to your meal.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2